Torque Analysis of Permanent Magnet Hybrid Stepper Motor using Finite Element Method for Different Design Topologies - E.V.C Sekhara Rao; P.V.N Prasad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper discusses about permanent magnet hybrid stepper motor magnetic circuit using finite element model for different geometric designs like uniform air-gap, non uniform air-gap, for different air-gap lengths, different tooth pitches and extra teeth on stator using PDE toolbox of Matlab at different current densities. Implementing these results in equivalent circuit model (permeance model), motor performance is analyzed for an existing motor for steady state conditions. These results suggest modifications for better performance of the PMH stepper motor like reduction of cogging torque and improvement in steady state torque with minimum THD.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.140